2020
DOI: 10.1111/conl.12718
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes toward biodiversity‐friendly greenspace management in Europe

Abstract: Increasing urbanization worldwide calls for more sustainable urban development. Simultaneously, the global biodiversity crisis accentuates the need of fostering biodiversity within cities. Policies supporting urban nature conservation need to understand people's acceptance of biodiversity‐friendly greenspace management. We surveyed more than 2,000 people in 19 European cities about their attitudes toward near‐natural urban grassland management in public greenspaces, and related their responses to nine sociocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 38 publications
4
36
0
Order By: Relevance
“…Still, these results are encouraging, as positive attitudes toward altered management are nonetheless an important prerequisite for considering grassland species during verge management in the first place. The results also echo those obtained from other anthropogenic habitats: the more familiar urban residents across Europe are with biodiversity, the more positive they are toward managing urban greenspaces in a biodiversity-friendly manner (Fischer et al 2020). Educating stakeholders on the grassland conservation value of road verges could thus be one of many steps toward reconciling road verge management with grassland conservation, especially as it was reported as highly feasible by the stakeholders themselves, as described earlier.…”
Section: Familiarity With the Role Of Road Verges As Potential Grasslsupporting
confidence: 73%
See 1 more Smart Citation
“…Still, these results are encouraging, as positive attitudes toward altered management are nonetheless an important prerequisite for considering grassland species during verge management in the first place. The results also echo those obtained from other anthropogenic habitats: the more familiar urban residents across Europe are with biodiversity, the more positive they are toward managing urban greenspaces in a biodiversity-friendly manner (Fischer et al 2020). Educating stakeholders on the grassland conservation value of road verges could thus be one of many steps toward reconciling road verge management with grassland conservation, especially as it was reported as highly feasible by the stakeholders themselves, as described earlier.…”
Section: Familiarity With the Role Of Road Verges As Potential Grasslsupporting
confidence: 73%
“…Although the values originally referred to in the context of cognitive hierarchy theory correspond to these abstract core values (Homer and Kahle 1988;Fulton et al 1996;Rawluk et al 2019), research has shown that the more tangible valued attributes are also useful in predicting attitudes (Manning, Valliere, and Minteer 1999;Seymour et al 2010). In habitat and vegetation management, attributes such as beauty (Gobster et al 2007), wildness or naturalness (Fischer et al 2020), cleanliness and evidence of deliberate caretaking (cues to care) (Nassauer 1995), are all suggested to correlate with attitudes toward particular management practices. On road verges, especially attributes such as traffic safety and neatness are suggested to drive attitudes toward different types of verge management (Akbar, Hale, and Headley 2003;Weber, Kowarik, and S€ aumel 2014;Hoyle et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Europe-wide study found that most people were favourable about such management when within well-defined areas, for example by regularly mowing edges (Fischer et al, 2020). These simple but under-utilised actions should be prioritised by pollinator conservation programmes, namely by communicating the benefits, and developing narratives that overcome social norms around tidiness (e.g.…”
Section: Opportunities For Increasing Uptake Of Pollinator Conservamentioning
confidence: 99%
“…Similarly, a 'Scout system could work on different levels passing on knowledge, from Beavers to Cubs to Scouts' and could 'help manage or create' naturalistic features, fostering ownership in the process. Time spent in naturalistic spaces and awareness of biodiversity conservation are positively related to acceptance of wilder, less manicured urban green spaces (Fischer et al, 2020), suggesting a positive feedback loop could emerge from outdoor lessons in local restored landscapes.…”
Section: From Passage To Placementioning
confidence: 99%